Restriction of the Global IgM Repertoire in Antiphospholipid Syndrome - Pashova, Shina; Balabanski, Lubomir; Elmadjian, Gabriel; Savov, Alexey; Stoyanova, Elena; Shivarov, Velizar; Petrov, Peter; Pashov, Anastas (Frontiers in Immunology, 2022)
The typical anti-phospholipid antibodies (APLA) in the anti-phospholipid syndrome (APS) are reactive with the phospholipid-binding protein β2GPI as well as a growing list of other protein targets. The relation of APLA to natural antibodies and the fuzzy set of autoantigens involved provoked us to study the changes in the IgM repertoire in APS. To this end, peptides selected by serum IgM from a 7 residue linear peptide phage display library (PDL) were deep sequenced. The analysis was aided by a novel formal representation of the Igome (the mimotope set reflecting the IgM specificities) in the form of a sequence graph. The study involved women with APLA and habitual abortions (n=24) compared to age-matched clinically healthy pregnant women (n=20). Their pooled Igomes (297 028 mimotope sequences) were compared also to the global public repertoire Igome of pooled donor plasma IgM (n=2 796 484) and a set of 7-mer sequences found in the J regions of human immunoglobulins (n=4 433 252). The pooled Igome from controls and APS patients was represented as a graph connecting the sequences with the longest common subsequence longer than 4 letters. This was a conservative estimate of the similarity between mimotopes of the same monoclonal antibody based on previously published data. In the resulting graph, identifiable clusters of vertices were considered putative footprints of overlapping antibody cross-reactivities. A subgraph based on those clusters which had significant over or underrepresentation of APS patients’ IgM mimotopes contained predominantly specificities underrepresented in APS. The differentially expressed IgM footprints showed an increased cross-reactivity with immunoglobulin J regions. The specificities underexpressed in APS had a higher correlation with public specificities than those overexpressed. The APS associated specificities were strongly related also to the human peptidome with 1 072 mimotope sequences found in 7 519 human proteins. These regions were characterized by low complexity. Thus, the IgM repertoire of the APS patients was found to be characterized by a significant reduction of certain public specificities found in the healthy controls with targets representing low complexity linear self-epitopes homologous to human antibody J regions.